Resilient IIoT Communication via Edge-Based Store-and-Forward and SLO Monitoring - Matias, José António; Macêdo, Raimundo José de Araújo (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2026)
Industrial Internet of Things (IIoT) systems integrate Operational Technology (OT) and Information Technology (IT) through distributed pipelines, but remain vulnerable to wide-area network (WAN) instability, which affects latency and reliability. This work-in-progress paper proposes an edge-based architecture that combines OPC UA–MQTT translation, a store-and-forward mechanism, and monitoring based on Service Level Objectives (SLO) to improve resilience. Preliminary simulation results show a reduction in latency from 23.21 ms (cloud, low load) to 3.77 ms at the edge, while maintaining system stability even under stress scenarios in which the cloud reached 961.97 ms. An increase in delivery reliability (94.3%) under failures is also observed, highlighting the benefits and trade-offs of edge buffering.